Peran Customer Service PT. Sriwijaya Air dalam Meningkatkan Pelayanan Di Bandara Soekarno-Hatta - Ahmad Ferdy Ramadhan (Universitas Majalengka, 2021)
Soekarno-Hatta International Airport is the main airport that serves flights to Jakarta, Indonesia. The airport is the most important means of air transportation for the sake of transportation both between islands and between countries. Soekarno-Hatta Airport is one of the gateways for the entry of domestic or international tourists. Limitation The problem in this study is the role of Customer Service in improving services at Soekarno-Hatta Airport. The purpose of this study is to explain how important the task of PT. Sriwijaya Air's Customer Service is in improving services at Soekarno-Hatta Airport. The method in this research is a case study for 2 months. The research is Customer Service in serving passengers. Customer Service has a role which is very important in the operation of airport activities, where Customer Service must provide information regarding departure schedules, arrivals, departure delays and departure cancellations. Customer Service in improving services must also know all the information needed by Soekarno-Hatta Airport users. efforts in carrying out their duties in order to improve services.